Pemberdayaan masyarakat Desa Sidoharjo dalam pemanfaatan minyak jelantah yang diolah menjadi lilin aromaterapi - Anatri Desstya; Alfi Yanit; Cita Aji Pangesti; Lestari Rahayu; Muharam Muharam; Adi Nugraha; Nur Yunianto; Prasetyo Dwi Utomo; Wahid Nur Ahmmadi; Yoga Annas Amrullah; Zakiyaturrahma Zakiyaturrahma; Nurul Hidayati; Rista Nurul Septiyani (Nur Science Institute, 2026)
Households in the village of Sidoharjo, Polanharjo Subdistrict, Klaten Regency, produce used cooking oil from daily cooking; however, this oil is discarded, which can lead to environmental pollution. The objective of this community service initiative is to provide education through outreach to owners of small and medium-sized enterprises (SMEs) producing rambak crackers and members of the PKK (Family Welfare Movement) in Sidoharjo Village, Polanharjo Subdistrict, Klaten Regency, regarding the utilization of used cooking oil to make aromatherapy candles. This initiative will be implemented in several stages: lectures, demonstrations, mentoring, and training. The implementation procedure consists of the preparation, implementation, and evaluation stages. The results of this community service project indicate an increase in knowledge regarding used cooking oil (its definition, properties, and impacts) and an understanding of candle-making (tools and materials, production steps, and products that can be made from used cooking oil). Each of these aspects improved from 67.8% to 97.1% and from 13% to 100%. Our project has successfully produced aromatherapy candles in various shapes, colors, and scents, including flower-shaped, star-shaped, and heart-shaped candles; red, yellow, and blue colors; and lemon, jasmine, and green tea scents.